Paradigm Lost: A Reasoned Review of the Literature on the Relationship between Ethics and Technological Innovation - Carignani, Andrea; Gemmo, Vanessa; Selmi, Jacopo (Advances in Social Sciences Research Journal, 2020)
In a society incontrovertibly shaped by information and communication technologies, individuals seem to find it increasingly difficult to acquire sufficient awareness of the consequences of their actions, and subsequently, develop a deep sense of ethical, social, and professional responsibility. Focusing on this fundamental aspect of the complex relationship between ethics and technological innovation, which James Moor defined as a “conceptual muddle”, this paper proposes a reasoned, although by no means exhaustive, review of 50 studies that explicitly cite Moor’s work and contribute, albeit with different objectives and methods, to a more in-depth examination of the relationship between ethical evaluations and emerging technologies. The papers considered in this review are distinguished by methodological approach and some particularly relevant and recurrent topics, namely policy vacuum, professional responsibility, ethical education, technological revolution, and privacy.